Soil fungal community is more sensitive than bacterial community to modified materials application in saline–alkali land of Hetao Plain - Bai, Xiaolong; Zhang, En; Wu, Jinmin; Ma, Donghai; Zhang, Chaohui; Zhang, Bangyan; Liu, Yunpeng; Zhang, Zhi; Tian, Feng; Zhao, Hui; Wang, Bin (Frontiers in Microbiology, 2024)
Soil salinization has become a major challenge that severely threatens crop growth and influences the productivity of agriculture. It's urgent to develop effectively management measures to improve saline-alkali soil. Thus, in this study, soil properties, microbial communities and function under DE (desulfurization gypsum), SA (soil amendment), FA (farm manure) and TA (coapplication of desulfurization gypsum, soil amendment and farm manure) in a field experiment were examined by high-throughput sequencing. The results showed that application of modified materials is an effective approach in improving saline-alkali soil, especially TA treatment significantly increased the content of AP, AK, SOM and AHN and decreased pH, BD and EC. The application of modified materials resulted notable enhancement in fungal diversity, altered fungal community composition and structure. Conversely, the effect on the bacterial community was comparatively minor, with changes limited to the structure of the community. With regards to fungal community composition, Ascomycota, Mortierellomycota, and Basidiomycota emerged as the dominant phyla across all treatments. At each taxonomic level, the community composition exhibited significant variations in response to different modified materials, resulting in divergent soil quality. TA treatment led to a decrease in Mortierellomycota but an increase in Ascomycota, which potentially enhances the capability to decompose organic matter and facilitate soil nutrient cycling. Additionally, the sensitivity of fungal biomarkers to modified materials surpassed that of the bacterial community.The impact of modified materials on soil microbial communities primarily stemmed from alterations in soil EC, AP, AK and SOM. FUNGuild analysis indicated that saprotroph trophic mode group was the dominant component, and application of modified materials notably increased the symbiotroph group. PICRUSt analysis revealed that metabolism was the most prevalent functional module observed at the pathway level 1. Overall, the application of modified materials led to a decrease in soil EC and an increase in nutrient levels, resulting in greater alterations in soil fungal community, but did not dramatically change soil bacterial community. Our study provides new insights into the application of modified materials in increasing soil nutrients and altering soil microbial communities and functions, and provides a better approach for improving saline-alkali soil of Hetao Plain.